STUDI KOMPARATIF METODE SAND BLASTING DENGAN BONDING AGENT DAN PERKUATAN WIREMESH PADA PERBAIKAN SELIMUT BETON - Andi Isdyanto; Rudy Djamaluddin; M. Wihardi Tjaronge; Rita Irmawaty, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
This research compares two repair methods for concrete cover spalling due to rebar corrosion: the Sand Blasting with Bonding Agent method and the Wiremesh Reinforcement method. The main objective is to evaluate the mechanical performance, bond strength (adhesion), and durability of the repaired concrete specimens. A quantitative experimental approach was used, creating and artificially damaging concrete beam specimens to simulate the damage. The damaged specimens were then repaired using the two methods. The first method involved cleaning the surface with sand blasting and applying a bonding agent before patching. The second method used wiremesh as external reinforcement, installed with anchors before applying the repair mortar. Both sets of repaired specimens were then comprehensively tested, including compressive strength, flexural strength, and bond strength tests. The results show that both methods significantly restore the structural integrity of the damaged concrete. However, the wiremesh reinforcement method demonstrated superior performance in enhancing the flexural strength and shear capacity in the repaired areas. Meanwhile, the sand blasting with bonding agent method showed excellent bond strength and was effective for more superficial damage. The study concludes that the sand blasting method is ideal for repairing local, non-structurally critical spalling, while the wiremesh method is more suitable for large-scale damage requiring increased structural capacity and crack resistance.